Analysis, Design and Optimization of Multilayer Antenna Using Wave Concept Iterative Process - Amri Houda (Institute of Advanced Engineering and Science, 2017)
The wave concept iterative process is a procedure used for analyses a planar circuits This method consists in generating a recursive relationship between a wave source and reflected waves from the discontinuity plane which is divided into cells. A high computational speed has been achieved by using Fast Modal Transform (FMT). In this paper we study a patch antenna and multilayer circuits, to determine the electromagnetic characteristics of these structures.